Assessment of Quality of Life in Liver Donors Following Donor Hepatectomy for Living Donor Liver Transplantation: Early experience from Nepal (Journal of Society of Surgeons of Nepal, 2025)
Introduction: Living donor liver transplantation is a life-saving procedure. The safety and outcome of healthy donors after donation remain an important concern, especially in low-volume centers from low- and middle-income countries. Limited data are available on donor quality of life and recovery in this setting.Methods: We conducted a cross-sectional observational study of living liver donors at at KIST Medical College Teaching Hospital, Lalitpur, Nepal. Donor health-related QOL was assessed using the short form health survey (SF-36) questionnaire, and postoperative concerns, return to work, and donor satisfaction were recorded. Descriptive statistics were used to summarize findings.Results: Eleven liver donors were included. The mean age of donors was 42.92 years, with 81.8% being female. The mean graft weight was 715.82 g, and the mean remnant liver percentage was 43.5%. Only one donor (9.1%) experienced a Grade II complication; the mean hospital stay was 9.3 days. The mean of the physical component score was 94.15, and the mean mental component score was 95.03. The most common postoperative concern was incisional pain (54.5%). Donors returned to their regular work at a mean of 3.8 weeks post-donation. All donors were satisfied with their decision to donate part of the liver.Conclusions: The quality of life of living donors at our center is comparable to high-volume well-established centers.